Advances in imaging to allow personalized medicine in Crohn's disease. (August 2015) - Neurath, Markus F
Highlights: New imaging modalities for mucosal inflammation and mucosal healing in Crohn's disease are available. Ultrasonography and magnetic resonance imaging are key imaging techniques. Molecular imaging in vivo holds promise for personalized medicine. Abstract : Crohn's disease is a destructive inflammatory bowel disease of unknown origin that may lead to various complications such as strictures, stenosis, fistulas and colitis-associated neoplasias. However, the course of the disease varies substantially among patients and disease behaviour may also change with time. At diagnosis behaviour is inflammatory in the majority of patients, while penetrating or structuring behaviour become more prominent at later time points. Thus, medication in Crohn's disease needs frequent optimization over time. Therefore, new strategies for prediction of response to therapy are urgently needed. Here, recent advantages in imaging techniques for personalized medicine in Crohn's disease are reviewed. Such advantages include ultrasonography, computed tomography, magnetic resonance imaging and new endoscopic approaches such as molecular endoscopy. It is expected that these novel techniques will lead to marked improvements in the assessment of disease behaviour and the prediction of response to clinical therapy with biologicals.